Effect of a joint on breakout noise characteristics of rectangular duct. Issue 3 (September 2019) - Jade, Nagaraja; Venkatesham, B
Breakout from a flexible rectangular duct depends on its structural properties as well as acoustic properties of the medium. Majority of duct breakout noise prediction models in the literature consider an ideal duct (without joint). However, ducts used in applications have joints. So, current research interest is to study the effect of duct joint in predicting the breakout noise and its influence on modal parameters. For this purpose, duct with a joint is considered in the experimental study and an ideal duct for numerical analysis. As a first step, an experimental setup is developed to measure breakout noise in terms of transverse transmission loss and radiation efficiency, and furthermore an experimental modal analysis is performed to measure modal parameters of the duct. Numerical analysis is performed on an ideal rectangular duct (without considering the joint condition) to calculate the breakout noise and modal parameters. Both, experimental and numerical results are compared, and it is observed that joint has a less significant influence on breakout noise as compared with modal parameters.